2018
DOI: 10.1016/j.foodchem.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and stabilization of oil-in-water nanoemulsions using a saponins-rich extract from argan oil press-cake

Abstract: In this study, we formulated and stabilized oil-in-water nanoemulsions using a crude extract from argan press-cake as sole emulsifier. Various extracts from argan press-cake were prepared in order to select the most surface-active one(s) foreseeing emulsions preparation. Fifty percent (v/v) ethanolic extract reduced the interfacial tension to a minimum value at both MCT oil and soybean oil interfaces (12.7 and 10.5 mN m respectively). This extract was also effective at producing fine emulsions with small dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 33 publications
6
50
0
Order By: Relevance
“…The negative surface potential value of emulsions stabilized by saponin was also observed in other works. This can be attributed to the carboxylic acid groups presented in the adsorbed saponin molecules [13,17]. Moreover, zeta potential results supported that saponin-coated particles were mainly stabilized by the electrostatic repulsion generated between the highly negatively charged droplets [31].…”
Section: Characterization Of Emulsionsmentioning
confidence: 79%
See 1 more Smart Citation
“…The negative surface potential value of emulsions stabilized by saponin was also observed in other works. This can be attributed to the carboxylic acid groups presented in the adsorbed saponin molecules [13,17]. Moreover, zeta potential results supported that saponin-coated particles were mainly stabilized by the electrostatic repulsion generated between the highly negatively charged droplets [31].…”
Section: Characterization Of Emulsionsmentioning
confidence: 79%
“…Nowadays, a significant challenge to be overcome in the field of emulsions is the introduction of natural products to act as surfactants [5,16,17]. This approach has been supported by the growth of consumer demands for more sustainable, natural, and environmentally friendly formulations, in line with the increasingly restrictive environmental legislation, in addition to the biocompatibility, biodegradability, and lower toxicity of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This substance can be delivered either solid or liquid forms that can be easily added to foods (Reichert, Salminen, Badolato Bönisch, Schäfer, & Weiss, 2019). Numerous recent reports have studied the formulation of NE using saponins as emulsifiers (Table 1), among them formulation of astaxanthin NE using ginseng saponins (Shu et al, 2018); gypenosides (Gps) isolated from the Gynostemma pentaphyllum tree, for astaxanthin NE (Chen et al, 2018b); formulation of NE using a saponin-rich extract from argan oil press-cake (Taarji et al, 2018b); and saponins extract from Verbascum nigrum L.…”
Section: Saponinsmentioning
confidence: 99%
“…It is important to report that the new research trends in the development of natural emulsifiers stabilized-NE are converging on the identification of new natural emulsifiers obtained from agrofood industrial by-products for sustainability development and resolving disposal of residues. In this context, Taarji et al (2018a) investigated the formulation of NE using a saponin-rich extract obtained from argan oil press-cake, as an emulsifier. These authors found that 50% ethanol extract diminished the interfacial tension to a low level in MCT and soybean oil (12.7 and 10.5 mN/m, respectively).…”
Section: Stability Of Nanoemulsionsmentioning
confidence: 99%
“…[98] Nanoemulsions are O/W and W/O emulsions with a droplet size of the dispersed phase from 20 to 500 [nm] [99] and they are kinetically stable. [103] Nanoemulsions can be used in the production of many types of cosmetic products, starting with water-like fluids, ringing gels, lotions, banner milks, crystal gels providing them various rheological, visual, and sensory properties. In comparison to microemulsions, nanoemulsions requires the use of small amounts of surfactant while maintaining a stable formulation.…”
Section: The Application Of Argan Oil In Cosmeticsmentioning
confidence: 99%